2006
DOI: 10.1017/s0033291706007409
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being: genetic and environmental contributions to stability and change

Abstract: For both males and females, long-term stability of SWB was mainly attributable to stable additive genetic factors, whereas susceptibility to change was mostly related to individual environmental factors. However, both stable environmental contributions and emerging genetic influences were indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
143
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 59 publications
16
143
1
3
Order By: Relevance
“…Both models reveal that common environmentalities have little influence on happiness. Indeed, model 1 estimates the value of c 2 at zero, a result consistent with estimates from other studies of well-being (Nes et al 2006). Common environmentalities play much more of a role in socioeconomic position and social support.…”
Section: Resultssupporting
confidence: 83%
“…Both models reveal that common environmentalities have little influence on happiness. Indeed, model 1 estimates the value of c 2 at zero, a result consistent with estimates from other studies of well-being (Nes et al 2006). Common environmentalities play much more of a role in socioeconomic position and social support.…”
Section: Resultssupporting
confidence: 83%
“…The genetic and environmental influence on the stable variance in a phenotype may be estimated, and correspondingly influences on change and development. Interestingly, several studies have reported high genetic influences on stability factors, but also genetic innovation -new genetic factors starting to operate at certain ages Nes et al, 2006). Fourth, the children of twins design involves offspring of MZ and DZ twins, and examines similarity across and within generations.…”
Section: Classic and Extended Twin Designsmentioning
confidence: 99%
“…S tím, jak se rozvíjí empirická věda o osobní pohodě, je však stále víc patrné, že se při jejím studiu nemůžeme omezovat jen na situaci, v níž se jedinec v daný okamžik nachází. Míra osobní pohody a spokojenosti je částečně výsledkem i dlouhodobých sociálně-psychologických procesů i genetických predispozic [Weiss, Bates, Luciano 2008;Nes et al 2006]. Do výzkumů osobní pohody a kvality života tak stále více proniká perspektiva životní dráhy [Chaloupková 2010].…”
unclassified
“…Ze soudobé odborné literatury je tedy patrné, že mentální zdraví a osobní pohoda jsou úzce propojeny, nepanuje však shoda, jak je přesně vymezit a jak vztah mezi těmito koncepty vypadá [Nes et al 2006]. Například Keyes [2007] chápe duševní poruchy a duševní zdraví a pohodu (flourishing) jako dvě odděle-né dimenze.…”
unclassified